2021
DOI: 10.1177/10755470211048480
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential of Inoculation Messages and Self-Affirmation in Reducing the Effects of Health Misinformation

Abstract: We investigated the effectiveness of inoculation and self-affirmation interventions in neutralizing effects of health misinformation. Women ( N=854) recruited via Prolific were randomly assigned to self-affirm (or not) and read an inoculation (versus control) message detailing five common attributes of misinformation. All participants read an article with misinformation about breast cancer screening and reported their reactions to the article. The inoculation (vs control) message reduced the negative effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…For example, research has found that inoculating people against conspiratorial arguments about vaccination before (but not after) exposure to a conspiracy theory effectively raised vaccination intentions 103 . Several recent reviews 102,104 and meta-analyses 105 have pointed to the efficacy of psychological inoculation as a robust strategy for conferring immunity to persuasion by misinformation, including many applications in the health domain 106 , such as inoculating people against misinformation about the use of mammography in breast-cancer screening 107 .…”
Section: Warn About the Mythmentioning
confidence: 99%
“…For example, research has found that inoculating people against conspiratorial arguments about vaccination before (but not after) exposure to a conspiracy theory effectively raised vaccination intentions 103 . Several recent reviews 102,104 and meta-analyses 105 have pointed to the efficacy of psychological inoculation as a robust strategy for conferring immunity to persuasion by misinformation, including many applications in the health domain 106 , such as inoculating people against misinformation about the use of mammography in breast-cancer screening 107 .…”
Section: Warn About the Mythmentioning
confidence: 99%
“…Social media companies have taken unprecedented steps amid the COVID-19 pandemic to control the spread of misinformation on their platforms, including attaching warning labels, removing content, and banning user accounts (Krishnan et al, 2021). There has also been a recent surge of research evaluating various techniques for mitigating the spread or impact of health misinformation with varying degrees of success (e.g., Iles et al, 2021;Pennycook et al, 2020;van der Linden et al, 2020;Vraga & Bode, 2020; W. Wang & Huang, 2020).…”
Section: Why People Believe Health Misinformation and Who Are At Risk...mentioning
confidence: 99%
“…For example, accuracy nudges have limited effects on reducing susceptibility to misinformation among conservatives (Rathje et al, 2022). Others attempted to use self-affirmation (i.e., confirming one's important values prior to information exposure) to reduce susceptibility to misinformation as a result of directionally-motivated reasoning with varying degrees of success (Iles et al, 2021;Szpitalak & Polczyk, 2019). It remains challenging to correct misperceptions if accepting misinformation is driven by preexisting beliefs or emotions.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Major misinformation themes included health (k=15) and climate change (k=7), the mean participant age distribution was 18 to 48 years, and most studies were conducted in the United States (k=28). A total of 31 studies reported misinformation credibility assessment [ 7 , 13 , 14 , 16 , 22 - 24 , 26 - 28 , 39 - 48 ], 26 reported real information credibility assessment [ 1 , 7 , 14 - 16 , 22 - 24 , 27 , 41 - 43 , 49 - 54 ], 12 reported credibility discernment [ 7 , 23 , 24 , 27 , 41 ], 12 reported misinformation sharing intention [ 7 , 13 , 23 , 40 , 45 , 50 ], 11 reported real information sharing intention [ 7 , 23 , 51 , 55 ], and 8 studies reported sharing discernment [ 7 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot for the effects of psychological inoculation on misinformation sharing intention (k=12). Different studies in the same article are distinguished by an underscore and the numbers 1 to 6 [ 7 , 13 , 23 , 40 , 45 , 50 ]. SMD: standardized mean difference.…”
Section: Resultsmentioning
confidence: 99%